The Contexts of Revelation: An In-Depth Study of Asbab Wurud Al-Hadith and Its Connection to Asbab Nuzul al-Quran - Sofyan, Nur Baety (El-Sunan: Journal of Hadith and Religious Studies, 2024)
This study aims to provide a comprehensive interpretation of the concept of Asbab Wurud al-Hadith, contemporary scholars' views, its classifications, and its connection to Asbab Nuzul al-Quran. Employing a library research method with a descriptive-analytical approach, the research involves gathering data, presenting scholarly perspectives, analyzing, and exploring the relationship between Asbab Wurud al-Hadith and Asbab Nuzul al-Quran. The study begins by defining Asbab Wurud al-Hadith and presenting the perspectives of contemporary scholars, followed by classifying the types of Asbab Wurud al-Hadith that underlie the delivery of specific hadiths by Prophet Muhammad (SAW). It also examines the interconnectedness of Asbab Wurud al-Hadith and Asbab Nuzul al-Quran, demonstrating how they complement one another in fostering a deeper understanding of Allah's (SWT) revelations and the sayings of Prophet Muhammad (SAW). The findings of this study can be summarized into three key points: First, Asbab Wurud al-Hadith is a branch of hadith studies focusing on the reasons behind the emergence of a hadith, whether driven by events, circumstances, or inquiries during its delivery by Prophet Muhammad (SAW). Contemporary scholars generally agree on its significance, albeit with varying opinions on the underlying factors of particular hadiths. Second, Asbab Wurud al-Hadith is divided into two categories: hadiths associated with specific causes (Asbab Wurud) and those without identifiable causes. Third, there is a strong correlation between Asbab Wurud al-Hadith and Asbab Nuzul al-Quran, as both serve similar roles in clarifying meanings, reconciling or prioritizing differing interpretations (tarjih), and providing explanations for the causes and implications of revelations. Furthermore, each can serve as a context for understanding the other.